2007
DOI: 10.1111/j.1365-313x.2007.03124.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of the hypersensitive response by an ATPase associated with various cellular activities (AAA) protein through suppression of a small GTPase, ADP ribosylation factor, in tobacco plants

Abstract: SummaryATPase associated with various cellular activities (AAA) proteins are commonly distributed among eukaryotes, and are involved in a multitude of cellular functions. NtAAA1 is one such example, being involved in pathogen response in tobacco plants. When its activity was suppressed in RNAi transgenic tobacco plants, an elevated resistance to the pathogenic bacterium Pseudomonas syringae was observed in comparison with the wild type. As AAA proteins function through interaction with specific partners, NtAAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Consistent with this, biochemical analysis confirmed that there was ATPase activity in the recombinant protein of OsAAA-ATPase1 ( Figure 6). Phylogenetically, OsAAA-ATPase1 was grouped within a subclade of proteins related to plant defense activation (Figure 1b), which included OsAAA-ATPase2-6 [12], tobacco NtAAA1 [18,19], and Arabidopsis AtOM66 [20]. These results suggest that OsAAA-ATPase1 belongs to the AAA-ATPase family.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Consistent with this, biochemical analysis confirmed that there was ATPase activity in the recombinant protein of OsAAA-ATPase1 ( Figure 6). Phylogenetically, OsAAA-ATPase1 was grouped within a subclade of proteins related to plant defense activation (Figure 1b), which included OsAAA-ATPase2-6 [12], tobacco NtAAA1 [18,19], and Arabidopsis AtOM66 [20]. These results suggest that OsAAA-ATPase1 belongs to the AAA-ATPase family.…”
Section: Discussionmentioning
confidence: 85%
“…AAA-type ATPases constitute a large protein family in a diverse range of organisms, and thus exhibit multiple and diverse cellular functions [15,33]. In plants, AAA-ATPase genes have been implicated in proteolysis [33], male meiosis [34], vacuolar maintenance [35], peroxisome biogenesis [36], morphogenesis [37], leaf senescence [29,38], and stress [28,39] and immune responses [18][19][20][21][22]. In this study, we present a novel rice AAA-ATPase gene member, OsAAA-ATPase1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No biological information is available for AT3G28510, whereas, for AATP1, one of its closest A. thaliana homologues, a role as a negative regulator of stress‐related genes has been suggested (Rama Devi et al ., ). Accordingly, the tobacco homologue NtAAA1 is involved in the attenuation of the hypersensitive response (Lee and Sano, 2007a, 2007b). We do not know the biological function of this tomato AAA‐type ATPase.…”
Section: Discussionmentioning
confidence: 99%